2022
DOI: 10.1002/lary.30009
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiation Therapy in Oral Cavity Verrucous Carcinoma

Abstract: Objectives/Hypothesis We investigate the clinicopathologic and treatment factors associated with the use of postoperative radiation therapy (PORT) and its effect on overall survival (OS) for patients with oral cavity verrucous carcinoma (VC). Study Design Retrospective cohort study. Methods A retrospective cohort study of the National Cancer Database (NCDB) from 2006 to 2015 was performed. Multivariable logistic regression was used to identify independent predictive factors associated with the use of PORT. Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 32 publications
4
36
0
1
Order By: Relevance
“…7 In a recent retrospective cohort study of the National Cancer Database (NCDB), Naik et al showed that positive surgical margins were associated with significantly worse overall survival (OS) (hazard ratio [HR] 2.85, P = 0.006). 82 However, in those patients the use of PORT showed no OS benefit (HR 3.12, P = 0.072). These findings suggest that the role of PORT is limited in oral verrucous carcinoma, favouring surgical re-resection, when feasible, over adjuvant radiotherapy in patients with adverse pathologic features or clinically overt residual tumour after surgery.…”
Section: Postoperative Radiotherapymentioning
confidence: 95%
See 3 more Smart Citations
“…7 In a recent retrospective cohort study of the National Cancer Database (NCDB), Naik et al showed that positive surgical margins were associated with significantly worse overall survival (OS) (hazard ratio [HR] 2.85, P = 0.006). 82 However, in those patients the use of PORT showed no OS benefit (HR 3.12, P = 0.072). These findings suggest that the role of PORT is limited in oral verrucous carcinoma, favouring surgical re-resection, when feasible, over adjuvant radiotherapy in patients with adverse pathologic features or clinically overt residual tumour after surgery.…”
Section: Postoperative Radiotherapymentioning
confidence: 95%
“…positive or close surgical margins, pT3–T4 primary tumour, perineural and lymphovascular invasion). 67 , 82 Analysing the SEER database, however, Mohan et al . demonstrated a statistically significant improvement in DSS in patients solely operated compared to those receiving surgery and PORT.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[10][11][12] Factors that contribute to the exceedingly favorable prognosis of HNVC are its well-differentiated grading and predominantly indolent behavior. 13 Close cooperation between the pathologist and surgeon is necessary to accurately diagnose HNVC which may appear histologically benign but clinically malignant. [14][15][16] Metastasis to cervical lymph nodes is a key prognostic factor in determining staging, survival, and remission outcomes following surgical resection of HNSCC independent of treatment with adjuvant radiotherapy (RT) or chemoradiotherapy.…”
mentioning
confidence: 99%